The Interplay Between 'Peacetime' Law and the Law of Armed Conflict: Consequences for Post-Conflict Peacebuilding. (27th April 2021) - Fleck, Dieter
Abstract: Focussing on the interplay between rules of international law applicable in peacetime and rules applicable during armed conflicts, this contribution examines the impact on the jus post bellum . In this context certain specific legal obligations are discussed to answer the question whether and if so, how their application post-conflict may be affected by the peacebuilding process after the (former) armed conflict. Essential norms of the protection of victims during armed conflicts continue to be relevant for peace operations and post-conflict peacebuilding. This includes guiding principles and effective measures of control for operational detentions; law enforcement operations to secure the security and safety of peacekeepers; the protection of the environment and efforts to strengthen the role of States and international organizations as well as their accountability in post-conflict reconstruction. The author demonstrates that jus post bellum requires due diligence during military operations, responsible planning and precautions. He submits that post-conflict peacebuilding should be characterized by pragmatic limitation, conciliation and participation of the parties. This suggests certain deviations from peacetime principles and rules, deviations that may include certain limits of protection which will, however, be balanced out by the temporary nature of peacebuilding measures. While such interplay between the different branches of international law remains subject to changing situations, a few general principles are considered to be relevant for the jus post bellum . Even if codification remains difficult, further case-oriented research is encouraged to confirm general principles and rules of this important branch of international law.